EVALUATING THE IMPACT OF NURSING ASSISTANT CERTIFICATION ON CLINICAL KNOWLEDGE AND PATIENT OUTCOMES - Mariam Dalli Aldhafeeri, Anwar Dalli Aldhafeeri, Habibah Alhadi Alruwaili, Tamam Gazim Nhar Alruwaili, Ohud Hattash Qayyadh Alruwaili, Sahar Malooh Al Ruwaili, Alya Hamoud Ageel Alshammari, (Chelonian Research Foundation, 2022)
Nursing assistants, also termed unlicensed assistive personnel, provide vitalbasic patient care in hospitals under the supervision of registered nurses. Certification programs aim to validate nursing assistants’ specialized knowledge and skills through standardized competency examinations. However, limited and inconsistent evidence exists regarding the impact of certification on nursing assistants’ knowledge, quality of care provided, and patient outcomes. This study evaluated potential effects of certification among nursing assistants working on medical-surgical units in two hospitals in Saudi Arabia. A cross-sectional comparison study design was utilized. Data collection involved a knowledge test and chart audits of 75 patients per group cared for by certified nursing assistants (n=25) versus uncertified nursing assistants (n=25). Certified nursing assistants demonstrated significantly higher scores on the clinical knowledge test (88% vs. 81%, p<0.05). Chart audits showed certified assistants had greater adherence to evidence-based care protocols for fall prevention (93% vs. 73%, p<0.01) and pressure ulcer prevention (96% vs. 84%, p<0.05) compared to uncertified assistants. Patients cared for by certified assistants had significantly lower fall rates (4% vs. 12%, p<0.05) and hospital-acquired pressure ulcer rates (8% vs. 20%, p<0.01). Findings provide important evidence supporting implementation of nursing assistant certification programs to enhance clinical knowledge, care quality, and patient outcomes.